Analisis Kualitas Air Sumur di RW 05 Kelurahan Banta-bantaeng Kota Makassar - S., Syamsudin; Rostina, Rostina; Billah, Usthum Al’Arif (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Makassar, 2025)
Water has become a primary necessity that is essential for humans to carry out their daily activities such as drinking, cooking, bathing, and even industrial processing, so that the function of water is not only limited to economic functions but also social functions. Water quality is determined by several factors, including physical factors such as temperature, turbidity, and dissolved solids. The purpose of this study is to determine the physical, chemical, and bacteriological quality of water in dug wells in Banta-Bantaeng Village, Rappocini District. This study is observational in nature with a descriptive approach. Based on the research, it was concluded that the physical, chemical, and bacteriological quality of dug well water in Banta-Bantaeng Village, Rappocini District, from each examination using 6 samples tested, the physical parameters did not meet the requirements, the chemical parameters met the requirements for each sample, and the bacteriological parameters showed 2 positive results containing MPN Coliform. Based on observations in the Banta-bantaeng Village area, several types of pollutants were found, namely toilets/septic tanks, sewers (domestic waste disposal), and pollution caused by the behavior of facility owners, who often wash and bathe around dug wells, causing the soil to become easily contaminated.